The electricity- and CO2-saving potentials offered by regulation of European video-streaming services. (February 2022) - Madlener, Reinhard; Sheykhha, Siamak; Briglauer, Wolfgang
Abstract: Massive increases in Internet data traffic over the last years have led to rapidly rising electricity demand and CO2 emissions, giving rise to environmental externalities and network congestion costs. One particular concern is the rise in data traffic generated by video-streaming services. We analyze the electricity-saving potential related to video streaming in Europe from 2020 to 2030. To this end, three trend scenarios (Business-as-usual, Gray, and Green) are considered and modeled bottom-up, taking specific electricity consumption (and trends) of data transmission networks, end-use devices, and data centers into account. Using these scenarios, we examine in more detail the approximate electricity-saving impact that regulatory interventions and technical standards can have on the electricity consumption of end-users, network operators, and data centers. The model results reveal that regulatory intervention can have a significant impact on electricity consumption and CO2 emissions of the residential houshold sector. Highlights: Scenario-based bottom-up analysis of energy consumption caused by video-streaming. Reveals that the need for and potential of regulatory intervention is significant. Energy efficiency gains cannot fully compensate the impact of data volume increase. Technical regulation can be an effective short-term measure and strategy. A mandatory data transit fee is proposed as the preferred long-term solution.